2017
DOI: 10.2147/oajct.s134555
|View full text |Cite
|
Sign up to set email alerts
|

Informing primary care physicians of patients' involvement in clinical trials carried out at a specialist care level

Abstract: Background: Patients enrolled in clinical trials continue to have frequent contacts with primary care physicians because of comorbidities or toxicities. The aim of the present study was to analyze the information provided at different levels, when participants are included in clinical trials organized at a specialized care level. The purpose was to verify if informing the patient's primary care physician is contemplated in the inclusion process. Methods:The authors conducted a cross-sectional study that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In one study, almost half (48%) of the 67 reviewed trials did not disperse wallet cards, while only four trials specified the method by which external providers should be informed of trial proceedings, typically by a letter. 7 The burden is then subsequently placed on the participant and family to have the capacity to recall use of the card and present it to the external provider. This leaves the participant and the trial highly vulnerable if this card is not presented and interventions are carried out that may be contraindicated to the investigational product or device.…”
Section: Current State Of Clinical Trial Safety Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, almost half (48%) of the 67 reviewed trials did not disperse wallet cards, while only four trials specified the method by which external providers should be informed of trial proceedings, typically by a letter. 7 The burden is then subsequently placed on the participant and family to have the capacity to recall use of the card and present it to the external provider. This leaves the participant and the trial highly vulnerable if this card is not presented and interventions are carried out that may be contraindicated to the investigational product or device.…”
Section: Current State Of Clinical Trial Safety Managementmentioning
confidence: 99%
“…The wallet card is portable, economical, and updated as needed but also can then be prone to wear and tear, lost, or forgotten. In one study, almost half (48%) of the 67 reviewed trials did not disperse wallet cards, while only four trials specified the method by which external providers should be informed of trial proceedings, typically by a letter 7 . The burden is then subsequently placed on the participant and family to have the capacity to recall use of the card and present it to the external provider.…”
Section: Current State Of Clinical Trial Safety Managementmentioning
confidence: 99%
“…Traditionally, the wallet card outlines the name of the Principal Investigator, a contact number, study sponsor, and title of the trial. A study of 67 trials showed only 48% provided cards and of participants interviewed at their primary care physician's office for ancillary care, only 15% even knew the title of the study in which they were participating (Schoenenberger et al, 2017). Antoni et al ( 2017) noted that in their cross-sectional study of 67 research protocols, less than half of studies even provided an identification card to participants.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, media used to communicate these details (such as wallet cards and Dear Provider letters) are fallible. 3 The novel use of wearable devices is now heralded as the next level of effective communication efforts related to disseminating safety information to healthcare providers outside the research team. 4,5 However, there is a gap in modeling the communication pathway of this safety-related information from the wearable device and the incorporation of the role of the nurse in supporting effective communication.…”
mentioning
confidence: 99%
“…Of paramount importance is the communication of safety-related information, such as contraindicated medications and side effects of investigative products. Yet, media used to communicate these details (such as wallet cards and Dear Provider letters) are fallible 3 . The novel use of wearable devices is now heralded as the next level of effective communication efforts related to disseminating safety information to healthcare providers outside the research team 4,5 .…”
mentioning
confidence: 99%